Libertad religiosa, laicidad estatal y derechos culturales: su materialización armónica. - Apáez Pineda, Oscar Javier (Hermenéutica, 2026)
This chapter analyzes the tension between the realization of cultural rights, religious freedom, and the principle of secularism in the Mexican constitutional order. Through an analysis of real social situations in which there is friction between the exercise of rights, it examines the draft resolution of the controversy raised in the amparo proceedings under review 215/2022 and 216/ 2022 before the Supreme Court of Justice concerning the installation of Christmas nativity scenes in public buildings and the removal from the Federal Labor Law of the right of agricultural workers to celebrate their regional festivals, generally linked to religious or patron saint celebrations, on their employers' premises. Following an introduction to the Mexican regulatory framework (religious freedom, cultural rights, and state secularism), the chapter examines the aforementioned cases, their context, and interpretations under the constitutional principles of state secularism, freedom of belief and religion, and cultural rights. The aim of this chapter is to elucidate how the Mexican legal system addresses the dilemma of protecting rich cultural diversity, which often has religious roots, without undermining the religious neutrality of the state or the freedom of belief of its citizens.